2014
DOI: 10.1016/j.bbamem.2014.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic simulations of anionic Au144(SR)60 nanoparticles interacting with asymmetric model lipid membranes

Abstract: Experimental observations indicate that the interaction between nanoparticles and lipid membranes varies according to the nanoparticle charge and the chemical nature of their protecting side groups. We report atomistic simulations of an anionic Au nanoparticle (AuNP(-)) interacting with membranes whose lipid composition and transmembrane distribution are to a large extent consistent with real plasma membranes of eukaryotic cells. To this end, we use a model system which comprises two cellular compartments, ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 47 publications
0
55
0
Order By: Relevance
“…For this reason, the interactions between AuNPs and biologically relevant molecules and aggregates such as those in cell membranes have been studied using both in vitro/vivo 1-7 and in silico 8-11 experiments. Other interaction partners of AuNPs considered in the literature include amyloids, 12 viruses, 13 bacteria, 14 proteins, 15, 16 and DNA.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the interactions between AuNPs and biologically relevant molecules and aggregates such as those in cell membranes have been studied using both in vitro/vivo 1-7 and in silico 8-11 experiments. Other interaction partners of AuNPs considered in the literature include amyloids, 12 viruses, 13 bacteria, 14 proteins, 15, 16 and DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the limitations in current CG models [53], atomistic models should be preferred, in principle, for the study of charged NPs. Akola and Vattulainen used all-atom simulations to investigate the initial stages of Au NP interaction with asymmetric lipid membranes as a function of NP charge [54,55]. They showed that cationic NPs bind spontaneously to both negatively charged and neutral (zwitterionic) lipid membranes, but binding to neutral membranes requires overcoming a 12 kJ/mol free energy barrier.…”
Section: Coated Gold Nanoparticles: Computational Studiesmentioning
confidence: 99%
“…[28] With regard to biomedical applications, a desirable property of gold nanoparticles is their ability to aggregate reversibly into nanoclusters of controlled size when placed in a special solution, and to dissociate back into individual nanoparticles when introduced into the body. [29, 30, 31, 32] Finally, we compare the binding affinity of Au 18 with those of Au 102 [33] and Au 144 [34, 35, 36, 37, 38, 39, 40, 32], functionalized by the same ligand under the same near-physiological conditions.…”
Section: Introductionmentioning
confidence: 99%